The influence of different crosslinking agents onto the physical properties, integration behavior and immune response of collagen-based barrier membranes - Ren, Yanru; Alkildani, Said; Burckhardt, Kim; Köwitsch, Alexander; Radenkovic, Milena; Stojanovic, Sanja; Najman, Stevo; Jung, Ole; Liu, Luo; Barbeck, Mike (Frontiers in Bioengineering and Biotechnology, 2025)
This study investigates the mechanical properties as well as in vitro and in vivo cyto- and biocompatibility of collagen membranes cross-linked with glutaraldehyde (GA), proanthocyanidins (PC), hexamethylendiisocyanate (HMDI) and 1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide/N-hydroxysuccinimide (EC/NHS). A non-crosslinked membrane was used as reference control (RF). The initial in vitro cytotoxic analyses revealed that the PC, EC, and HMDI crosslinked membranes were cytocompatible, while the GA crosslinked membrane was cytotoxic and thus selected as positive control in the further in vivo study. Cross-linking enhances the tensile strength and collagenase resistance, effectively prolonging the membrane’s standing time in vivo. Using (immune-) histochemistry and histomorphometrical analyses, the cellular inflammatory responses, tissue integration and vascularization patterns at 10-, 30-, and 90-day post-implantation in a subcutaneous implantation model in rats were analyzed. The PC membrane elicited the mildest inflammatory cell levels, akin to the RF membrane, while other groups induced an M1-dominated macrophage response and numerous multinucleated giant cells throughout the study period. EC membranes maintained structural stability up to 30 days post-implantation, similar to the GA group, whereas others collapsed prematurely. Concurrent with membrane collapse, transmembrane vascularization occurred across all groups. Histopathological and histomorphometry results reveal the intricate interplay of inflammatory cell populations in vascularization. These findings offer valuable insights into the pivotal role of cross-linkers in modulating mechanical properties and tissue responses of collagen membranes.